2007
DOI: 10.1108/09604520710735164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of service quality dimensions on behavioural purchase intentions

Abstract: PurposeThis paper seeks to examine the relationship between service quality and behavioural purchase intentions in the public‐sector transport industry in Spain.Design/methodology/approachThe study first identifies five distinctive research streams in service quality. An empirical analysis is then carried out in which the SERVPERF scale is adapted to the study of service quality in the public‐sector transport industry. The study then examines the relationship between service quality and purchase intention usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 86 publications
3
28
0
11
Order By: Relevance
“…Notably, the inclusion of scale items which evaluate perceptions of employee interaction, which represents a key component of the standardised SERVQUAL and SERVPERF approaches and has been found to be an identifiable issue in transport services (Pérez et al 2007;Chou et al 2014;Carreira et al 2014), will allow for the importance of this dimension to be evaluated. Moreover, the current approach taken by the Scottish Government, whilst covering a multi-item measurement scale for service quality and a single item measurement scale for service satisfaction, excludes ancillary concepts of service provision such as service retention and service loyalty in the case of existing customers as well as service intention in the case of non-bus users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the inclusion of scale items which evaluate perceptions of employee interaction, which represents a key component of the standardised SERVQUAL and SERVPERF approaches and has been found to be an identifiable issue in transport services (Pérez et al 2007;Chou et al 2014;Carreira et al 2014), will allow for the importance of this dimension to be evaluated. Moreover, the current approach taken by the Scottish Government, whilst covering a multi-item measurement scale for service quality and a single item measurement scale for service satisfaction, excludes ancillary concepts of service provision such as service retention and service loyalty in the case of existing customers as well as service intention in the case of non-bus users.…”
Section: Discussionmentioning
confidence: 99%
“…Utilising the SERVPERF measurement approach, Abdullah et al (2012) alternatively find that the dimensions of tangibility, reliability and assurance to be the most important in the evaluation of service quality by airline passengers. In the context of bus transit, Pérez et al (2007) find that the five service dimensions of service quality measured in SERVPERF can be identified and that each holds an effect over purchase intention. Interestingly, their analysis also suggests that the dimensions of service quality may reach a saturation level with customers, whereby additional service enhancements do not generate increased patronage.…”
Section: Transport Applicationsmentioning
confidence: 99%
“…Existing research on service quality analyses In recent years, the management of service quality has attracted considerable attention from academics who have investigated the characteristics of service quality (e.g., Golder et al 2012;Harvey 1998), the effect of service quality on behavioral intentions (e.g., Tripp and Drea 2002;Sánchez Pérez et al 2007), and the impact of service quality on operational and business performance (e.g., Adam 1994). Consequently, public transport operators as well as other service providers have begun to use quality measures for various quality management purposes.…”
Section: Measurement and Analyses Of Service Qualitymentioning
confidence: 99%
“…In recent years, the management of public transport quality has attracted considerable attention from academics investigating the measurement of service quality (Prioni and Hensher 2000;, the effect of service quality on behavioral intentions (e.g., Tripp and Drea 2002;Sánchez Pérez et al 2007), or the design of performance-based quality contracts (Hensher and Stanley 2003;Hensher and Houghton 2004). Likewise, public transport operators are increasingly focusing on improving service quality, assuming that this has an impact on their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Perez, Abad, Carrillo, & Fernandez, 2007;Dabholkar, Shepherd, & Thorpe, 2000) have shown the relationship between service quality and behavioural purchase intention or behavioural intention. Perez et al (2007) indicated that there are five dimensions of service quality which comprise tangibility, reliability, receptivity/responsiveness, assurance and empathy. These dimensions are also associated with the individual's behavioural intention to use the service provided.…”
Section: Behavioural Intention and Service Qualitymentioning
confidence: 99%